Pensamientos negativos y su incidencia en el desarrollo de depresión en una mujer de 19 años de la ciudad de Guayaquil - Balladares Peña, Carla Fabiola (2022)
Having negative thoughts is normal, it is something that is present in the lives of all people throughout life, but you have to know how far to allow those thoughts that are largely harmful to be part of life, because if they are negative thoughts in excess, in the long run they cannot be controlled to the point of becoming somatized, physical discomfort, so many people do not have a quality life because they do not control them, leading to problems. That is why this case study is based on treating negative thoughts and their incidence in the development of depression in a 19-year-old woman from the city of Guayaquil. Which was allowed to reach a diagnosis with the help of different techniques, such as clinical observation, semi-structured interview and with tools such as clinical history, observation guide, among others. The way in which negative thoughts affect the patient's depression will be analyzed, giving a diagnosis based on the criteria of the ICD-10 F32.1 Depressive disorder in a moderate episode, a therapeutic plan with a cognitive behavioral approach is recommended, using techniques to reduce the symptoms and modify the different distorted thoughts of the patient.